Sales management success : optimizing performance to build a powervul sales team - Kurzrock, Warren (John Wiley & Sons, Inc., 2020)
Well-grounded in research and real-world experience, as well as proven ideas and tools, this thorough resource contains a leading-edge training program that is filled with state-of-the-art approaches specifically designed for sales managers. --